2015
DOI: 10.1016/j.jgo.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinical parameters predictive of one-year survival using two geriatric tools in clinically fit older patients with hematological malignancies: Major impact of cognition

Abstract: Little is known about the reliability of G8 screening tool and the prognostic value of clinical parameters within the Comprehensive Geriatric Assessment (CGA) in clinically fit older patients with haematological malignancies. This study was performed to assess the reliability of G8 as a screening tool and to determine the predictive value of CGA items in terms of one-year overall survival (OS). G8 and CGA were proposed to 107 consecutive patients (65-89yrs) with haematological malignancies that were judged cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 39 publications
1
50
0
1
Order By: Relevance
“…37 Dementia detected as part of a geriatric evaluation was associated with poor survival among German patients with chronic lymphocytic leukemia (n = 97), 20 and cognitive impairment was predictive of mortality among 107 ostensibly clinically fit older Belgian patients with different blood cancers (hazard ratio, 3.26; 95% CI, 1.04-10.19). 19 In the United States, Klepin and colleagues 21 found that inpatients with acute myelogenous leukemia with impaired cognition had worse overall survival (n = 74).…”
Section: Discussionmentioning
confidence: 99%
“…37 Dementia detected as part of a geriatric evaluation was associated with poor survival among German patients with chronic lymphocytic leukemia (n = 97), 20 and cognitive impairment was predictive of mortality among 107 ostensibly clinically fit older Belgian patients with different blood cancers (hazard ratio, 3.26; 95% CI, 1.04-10.19). 19 In the United States, Klepin and colleagues 21 found that inpatients with acute myelogenous leukemia with impaired cognition had worse overall survival (n = 74).…”
Section: Discussionmentioning
confidence: 99%
“…In several previous studies that analyzed the association between the G8 score and OS, the cut-off value of G8 was set as 14 points [6, 12, 13, 21]. Kenis et al reported that patients with a G8 score of ≤14 significantly survived less than patients with a score of >14 in 937 elderly patients with various types of cancer [6].…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study of haematological malignancy survivors found that those with any cognitive impairment had a one-year overall survival of 63% compared to 83% for those with no cognitive impairment (hazard ratio 3.2 85% confidence interval 1.04-10.19) (Dubruille et al 2015). However, the independent value of these findings needs to be confirmed in studies that control for confounding variables including comorbidities.…”
Section: Clinical Implications Of Crcimentioning
confidence: 99%
“…Haematological malignancies are usually systemic, and often treated with chemotherapeutic agents that have been implicated in CRCI in solid tumours. The growing literature in this area suggests that cognition is an important predictor of survival in patients with haematological malignancies (Dubruille et al, 2015) and therefore, understanding factors that lead to CRCI in haematological malignancies warrants attention.…”
mentioning
confidence: 99%